The Closure of Isbat For Polygamous Marriage on Legal Purpose Perspective - Alhaidar, Nihrul Bahi; Muhajir, Muhammad; Dhuha, Syamsud (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2023)
After attendance, the enactment of the Supreme Court Circular (SEMA) Number 3 of 2018 answers the legal vacuum over isbat for Polygamous marriage. But in practice, the SEMA confuses its implementation. This study aims to analyze the application of polygamous marriage law in SEMA number 3 of 2018 and the juridical implications for justice, expediency, and legal certainty. This research includes normative legal research with statutory and conceptual approaches. Gustav Radbruch's theory of legal purpose is used as his analysis knife. The study concluded that closing the door of Isbat for Polygamous marriage is not the right solution because marriage isbat is one way to obtain legal guarantees in the eyes of the state. The aggrieved subject of the SEMA was a polygamous wife who could not take legal action in seeking justice. Judging from Gustav Radbruch's theory, SEMA number 3 of 2018 has not met the elements of legal objectives. The provisions in SEMA number 3 of 2018 only accommodate the interests of children. The rights of polygamous wives should be prioritized because the benefits received are more significant than tightly closing the door of isbat for Polygamous marriage. It is necessary to review SEMA number 3 of 2018 to contain concrete values of justice, expediency and legal certainty for children and wives.